The Influence of Knowledge and Attitudes on Snack Industry Consumption on the Nutritional Status of Students Nutrition Program , University Of Muhammadiyah Bima - Dea Zara Avila; Alkhair; Nur Husnul Khatimah; Muammar Iksan (Science Midwifery, 2023)
They go to campus, thus increasing the likelihood of buying snacks is higher. As well as foods that are often consumed by students are industrial snacks which contain more carbohydrates, so they can cause other nutritional deficiencies. Foods that are often consumed by students are industrial snacks which contain more carbohydrates so that they can cause other nutritional deficiencies. Wrong eating habits in adolescence will have an impact on nutritional status. Malnutrition can reduce the body's resistance to disease, increase the incidence of disease (morbidity), reduce the level of intelligence and productivity. Meanwhile, nutrition is more associated with degenerative diseases at a younger age and the tendency for adolescents to experience obesity (Emilia et al., 2021). The purpose of this research is to know the effect of knowledge and attitudes on consumption of industrial snacks on the nutritional status of students of the University Of Muhammadiyah Bima Nutrition Study Program. This research was conducted at University Of Muhammadiyah Bima from November 12 to November 30, 2022. This type of research is a cross-sectional study. The population in this study were all students of the first semester of the nutrition study program with the sample selection using the accidental sampling method, namely 71 people. Data on nutritional status were taken by measuring student height and weight, and knowledge and attitudes towards snack consumption were measured using a questionnaire. Then the data were analyzed using the SPSS application using the Chi-Square test. The research results showed that there was a relationship between knowledge (P = 0.016) and attitude (0.006) consumption of industrial snacks on the nutritional status of University Of Muhammadiyah Bima nutrition study program students. This researcher hope that this study can increase the readers’ awarness and knowledge about the consumption of industrial snacks in order to avoid various diseases related to snack consumption, such as obesity.